Carbon Dioxide Seabed Storage Technology and Development - Wang, Biyuan (Transactions on Engineering and Technology Research, 2024)
With the acceleration of global industrialization, the massive use of fossil fuels led to a sharp rise in atmospheric CO2 concentrations, triggering a series of environmental problems such as global warming and sea level rise. As an important component of carbon capture, utilization, and storage (CCUS) technology, offshore carbon sequestration held significant importance for achieving global emission reduction targets. This study focused on CO2 seafloor storage technology and its development, describing four methods of CO2 ocean storage: ocean water column storage, ocean sediment storage, CO2 replacement gas hydrate storage, and ocean fertilization. The feasibility of seabed sequestration technology was discussed from three perspectives: policy background, economic costs and benefits, and technological application conditions. Additionally, the study analyzed the bottlenecks in applying this technology and proposed coping strategies. As an indispensable part of the CCUS strategy, offshore carbon sequestration played a crucial role in achieving global greenhouse gas (GHG) emission reduction targets.